Effect of Suryanamaskar Practice on Selected Physical Fitness Variables Among Male District-Level Volleyball Players of Kashmir - Towheed Ahmad Wagay; Dr. Chanderkant Dhiman (PT. Radja Intercontinental Publishing, 2026)
The purpose of the present study was to examine the effect of Suryanamaskar practice on selected physical fitness variables among male district-level (Bandipora) volleyball players of Kashmir. Fifteen male volleyball players aged between 15 and 20 years were selected through simple random sampling. The study employed a single-group pre-test and post-test research design. The selected participants underwent a structured Suryanamaskar training programme for six weeks, five days per week, with each session lasting 30–45 minutes. The dependent variables selected for the study were speed, agility, and flexibility. Speed was measured using the 50-Meter Dash Test, agility through the Shuttle Run Test, and flexibility through the Sit-and-Reach Test. Descriptive statistics, including mean and standard deviation, were computed, while a dependent-samples t-test was used to determine the significance of differences between pre-test and post-test scores at the 0.05 level of significance. The results revealed a significant improvement in agility (t = 3.25, p < 0.05) and flexibility (t = 7.95, p < 0.05) following the Suryanamaskar intervention. However, the improvement in speed was not statistically significant (t = 0.46, p > 0.05). The findings indicate that regular Suryanamaskar practice effectively enhances agility and flexibility among volleyball players but has limited influence on speed performance. Therefore, Suryanamaskar may be incorporated as a supplementary training modality in volleyball conditioning programmes to improve selected components of physical fitness. The study concludes that traditional yogic practices can serve as cost-effective and scientifically supported methods for enhancing athletic performance and physical fitness.